b/a x + a/b y = a2 + b2 , x+y =2ab solve for x and y

Here is the link given below for the answer to your query :

Please follow the part (e) of the given link :

https://www.meritnation.com/ask-answer/question/i-am-a-paid-user-of-meritnation-q-solve-each-of-the-followin/pair-of-linear-equations-in-two-variables/807893

  • 5

bx/a + ay/b = a2 + b2 ......... eq1

x + y = 2ab .... eq 2..

frm eq 1.. b2x + a2y / ab = a2 + b2

-> b2x + a2y = a3b + b3a

-> b2x - b3a = a3b - a2y

->b2 ( x - ab ) = a2 ( ab - y )

-> frm eq 2 ... b2 ( x - x/2 + y/2 ) = a2 ( x/2 + y/2 - y )

-> b2 ( x/2 - y/2 ) = a2 ( x/2 - y/2 )

-> b2x - b2y = a2x - a2y

-> x ( b2 - a2 ) = y ( b2 - a2 )

-> x = y ..

put the value of x in eq 2.... 2y = 2ab

hope this will help!

  • 57

bx/a + ay/b = a2 + b2 ......... eq1

x + y = 2ab .... eq 2..

frm eq 1.. b2x + a2y / ab = a2 + b2

-> b2x + a2y = a3b + b3a

-> b2x - b3a = a3b - a2y

->b2 ( x - ab ) = a2 ( ab - y )

-> frm eq 2 ... b2 ( x - x/2 + y/2 ) = a( x/2 + y/2 - y )

-> b2 ( x/2 - y/2 ) = a2 ( x/2 - y/2 )

-> b2x - b2y = a2x - a2y

-> x ( b- a2 ) = y ( b2 - a)

-> x = y ..

put the value of x in eq 2.... 2y = 2ab

hope this will help!

  • 11

bx/a + ay/b = a2 + b2 ......... eq1

x + y = 2ab .... eq 2..

frm eq 1.. b2x + a2y / ab = a2 + b2

-> b2x + a2y = a3b + b3a

-> b2x - b3a = a3b - a2y

->b2 ( x - ab ) = a2 ( ab - y )

-> frm eq 2 ... b2 ( x - x/2 + y/2 ) = a2 ( x/2 + y/2 - y )

-> b2 ( x/2 - y/2 ) = a2 ( x/2 - y/2 )

-> b2x - b2y = a2x - a2y

-> x ( b2 - a2 ) = y ( b2 - a2 )

-> x = y ..

put the value of x in eq 2.... 2y = 2ab

hope this will help!

  • 9
What are you looking for?